Present status and future criticalities evidenced by an integrated assessment of water resources quality at catchment scale: The case of Inle Lake (Southern Shan state, Myanmar). (May 2018) - Re, Viviana; Thin, Myat Mon; Setti, Massimo; Comizzoli, Sergio; Sacchi, Elisa
Abstract: Assessing aquifer dynamics and groundwater interactions with surface waters are prerequisite for the correct management of water resources in the long-term, especially under the increasing pressure of climate change and the growing freshwater demand. This work presents the results of the first integrated assessment in the Inle Lake catchment aimed at understanding the surface and groundwater dynamics and the impact of agriculture and tourism on water quality. Results of an investigation performed in winter 2015, targeting the water chemical and isotopic (δ 18 OH2O and δ 2 HH2O ) composition, and soil mineralogy, confirmed that Inle is an alkaline lake, where carbonate equilibria dominate its hydrochemistry. The high resilience of the lake to external perturbations is due to calcite precipitation, that represents an effective mechanism of P removal and, combined to the low residence time of water, prevents the accumulation of nutrients in lake waters. The investigation also permitted the first characterization of groundwater in the region, highlighting the dominance of Mg(Ca)-HCO3 facies . Two deep groundwater circulations could be evidenced: one of high temperature, Na-HCO3 type (Khaung Daing Hot Spring) and one in equilibrium with the dolomitic rocks of the basement, upwelling along a fault zone oriented N-S in the Northern part of the basin. The latter groundwater contributes to Inle lake by mixing with local recharge in the aquifer and by feeding the network of artificial channels created for reclamation purposes. Evidencing recharge mechanisms of both surface and groundwater makes it possible to highlight the impact of seasonal fluctuations of the water levels, and the associated flooding of some sectors of the catchment, on the Inle Lake agroecosystems and to evaluate possible scenarios for the future sustainable development of the region. Graphical abstract: Image 1 Highlights: First quality assessment of water resources targeting the Inle Lake catchment. Inle is a highly resilient alkaline lake, where carbonate equilibria dominate. Groundwater in the region is mainly of Mg(Ca)-HCO3 type. Two different deep groundwater types upwell along fractures in the basin. Groundwater feeds Inle Lake by contributing to the surface water network.